2019
DOI: 10.18087/cardio.2019.2.10231
|View full text |Cite
|
Sign up to set email alerts
|

Hypolipidemic Therapy and Chronic Kidney Disease: Effects on Cardiovascular Risks and Renal Dysfunction

Abstract: Steady increase in the prevalence of chronic kidney disease (CKD) is a serious public health problem, since CKD potentially leads to the development of end-stage renal disease (ESRD) that requires high-cost replacement therapy and is closely associated with increased risk of developing cardiovascular diseases (CVD), which are the cause of death in most patients. Progression of renal dysfunction and development of CVD are significantly affected by hyper- and dyslipidemia. This review contains results of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…As the global population ages at an unprecedented rate, the incidence of chronic diseases is soaring, and chronic kidney disease (CKD) is no exception ( 1 ). The more patients suffer from CKD, the more develop end-stage renal disease (ESRD) ( 2 ). ESRD is diagnosed when kidney function is insufficient to sustain life without kidney transplantation or dialysis ( 3 ), and its prevalence is also rising ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…As the global population ages at an unprecedented rate, the incidence of chronic diseases is soaring, and chronic kidney disease (CKD) is no exception ( 1 ). The more patients suffer from CKD, the more develop end-stage renal disease (ESRD) ( 2 ). ESRD is diagnosed when kidney function is insufficient to sustain life without kidney transplantation or dialysis ( 3 ), and its prevalence is also rising ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dyslipidemia is defined as the imbalance of cholesterol, low-density lipoprotein cholesterol, triglycerides, and high-density lipoprotein. It is seen as a key risk factor in the formation and development of cardiovascular disease, stroke heart failure, and renal failure [ 2 , 3 ]. A national survey showed that the overall prevalence of dyslipidemia among Chinese adults is steadily rising [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease is an important public health problem (1), with 8-10% of the adult population having some form of kidney damage (2). According to the Turkish Society of Nephrology Registry Report, end-stage renal disease (ESRD) prevalence is 957 per million population in Turkey in 2017 (3).…”
Section: Introductionmentioning
confidence: 99%